From Case Reports to Molecular Insight: Examining the Outcomes and Underlying Mechanisms of Squamous Cell Carcinoma in Breast Implant Patients—A Systematic Review - Camicia, Alexandra; Foppiani, Jose A.; Raska, Otakar; Hernandez Alvarez, Angelica; Lee, Daniela; Taritsa, Iulianna C.; Schuster, Kirsten A.; Wan, Rou; Neradová, Sylva; Lin, Gavin J.; Lee, Theodore C.; Molitor, Martin; et al. (International journal of molecular sciences, 2024)
There is extensive coverage in the existing literature on implant-associated lymphomas like anaplastic large-cell lymphoma, but breast implant-associated squamous cell carcinoma (BIA-SCC) has received limited scholarly attention since its first case in 1992. Thus, this study aims to conduct a qualitative synthesis focused on the underexplored association between breast implants and BIA-SCC. A systematic review was conducted utilizing the PubMed, Web of Science, and Cochrane databases to identify all currently reported cases of BIA-SCC. Additionally, a literature review was performed to identify potential biochemical mechanisms that could lead to BIA-SCC. Studies were vetted for quality using the NIH quality assessment tool. From an initial pool of 246 papers, 11 met the quality criteria for inclusion, examining a total of 14 patients aged between 40 and 81 years. BIA-SCC was found in a diverse range of implants, including those with smooth and textured surfaces, as well as those filled with saline and silicone. The condition notably manifested a proclivity for aggressive clinical progression, as evidenced by a mortality rate approximating 21.4% within a post-diagnostic interval of six months. Our literature review reveals that chronic inflammation, driven by various external factors such as pathogens and implants, can initiate carcinogenesis through epigenetic modifications and immune system alterations. This includes effects from exosomes and macrophage polarization, showcasing potential pathways for the pathogenesis of BIA-SCC. The study highlights the pressing need for further investigation into BIA-SCC, a subject hitherto inadequately addressed in the academic sphere. This necessitates the urgency for early screening and intervention to improve postoperative outcomes. While the review is confined by its reliance on case reports and series, it serves as a valuable reference for future research endeavors.